REVEALING A CASE GRAMMAR IN THE FILM “WHERE DO WE GO NOW” BASED ON FILLMORE’S PERSPECTIVE - Basid, Abdul; Lestari, Ega; Izza, Fahim Himami; Noer, Daffa Lazuardy (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
This study aims: (1) to reveal the modalities in the film “Where Do We Go Now” directed by Nadine Labaki based on the perspective of Charles J. Fillmore; (2) to reveal the propositions in the film “Where Do We Go Now” directed by Nadine Labaki based on the perspective of Charles J. Fillmore. This research is descriptive qualitative research. The data source in this study is the film “Where Do We Go Now” directed by Nadine Labaki with a duration of 110 minutes and produced by Les Films des Tournelles, Pathe, Les Films de Beyrouth in 2011. The data collection techniques in this study used watching and taking note techniques. The data validation technique in this study uses several steps, namely increasing persistence, triangulation, and discussion. This study has the following results: (1) there are two types of modalities in the form of a tense modality and an adverb modality; and (2) there are five types of propositions in the form of agentive case, objective case, source case, locative case, and time case.